The impact of interference of the executive arm of government in the choice of the principal officers at the sub-national legislature, in Nigeria’s Fourth Republic: Kwara and Osun states in focus - Abdulwahab, Alhaji Kayode; Ambali, Abdul Rauf; Salahu, Moshood Olayinka (Faculty of Administrative Science and Policy Studies, 2024)
This paper investigates the impact of interference by the executive arm of government, in the choice of the leadership at the sub-national legislature, in Nigeria’s Fourth Republic. And the focus was on Kwara and Osun States, intending to establish, or otherwise, the veracity of this claim. The objective thereby is to engender independence of the two arms of government, which is the panacea to the entrenchment of the principle of checks and balances: as the catalyst for good governance. The triangular method was adopted. The findings show that the Governors, through the instrumentality of the ruling party, exercise overwhelming influence in the nomination of candidates to the two State Houses of Assembly. In addition, the humongous bureaucratic, security and financial resources at their disposal give them leverage to interfere in the choice of the principal officers. The paper recommends that the legislature, like the executive arm at the sub-national level, should have financial autonomy. This would embolden them to take independent decisions on critical matters, including, the choice of their principal officers, without the fear of repercussion and being financially strangulated by Governors. Furthermore, the ruling party should enforce party supremacy, and not be at the dictates of the Governor.